Analyzing the effects of special washing processes on characteristics of sewing threads - CEVİZ, NURAY (TAYLOR & FRANCIS LTD, 2017)
In recent years, wet (washing, bleaching, etc.) and dry (abrasive, laser shaping, rodeo, etc.) operations applied on fashion denim products have become an important factor to increase the added value. However, these wet and dry processes applied to the denim products may have adverse effects on the strength of the fabric and other supplementary materials of denim products. For example, thread breakages affect the repair ratios and quality of products, which causes time and profitability losses in companies. The main objective of this study is to analyse how the types of washing affect the strength of the sewing threads that are commonly used in the production of denim trousers. In this study, 100% cotton denim fabric with a weight of 11.5 ounces and two different sewing threads were used. The fabrics are sewn as trouser legs with chain and lock stitch. Five different washes were applied to the trouser legs. The obtained data were evaluated in the R statistical program. As a result of the analyses made it is proven that the washing techniques used have an effect on the sewing threads' tensile strength and elongation at break. The tensile strengths of lock stitch and chain stitch decrease averagely 35% and elongation at break of lock stitch decreases %22 and chain stitch decreases 29.8%.
Keywords: Sewing; sewing threads; denim washing; stone washing; bleaching; NEEDLE